Studi Empiris Terkait Loyalitas Pelanggan pada Bisnis Coffee Shop - Wijaya, Vanessa; Widjaja, William (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: The rapid growth of coffee outlets in Indonesia has increased competition in this industry, thus encouraging each coffee outlet to continue to innovate with superior products that differentiate it from competitors. This research aims to analyze the influence of brand equity on customer loyalty at Kopi Nako outlets, by considering the role of purchasing intention variables and purchasing decisions as intervening variables. Research Methodology: The research method used is ex-post facto with a quantitative approach. The sampling technique used is non-probability sampling with a purposive sampling method based on the population. Data was collected through questionnaires given to 104 respondents, who were consumers of Kopi Nako or had interacted directly with the Kopi Nako brand. Results: The findings of this research reveal that there is a positive and significant influence between brand equity on customer loyalty through purchase intentions and purchase decisions. Limitation: 1. The number of respondents is only limited to 104 respondents, researchers believe that involving a larger number of respondents can increase the level of accuracy and representation of research results. 2. The research variables that are the focus of this research are limited to brand equity, purchase intention, purchase decision, and customer loyalty. There are various other factors that might influence customer loyalty in the context of Kopi Nako, such as customer satisfaction, word-of-mouth (WOM), and marketing mix. Contribution: The achievements of this research can contribute to the understanding of marketing theory, especially in the context of the relationship between brand equity, purchase intention, purchase decisions, and customer loyalty. Apart from that, marketing practitioners, especially those in the coffee industry such as Kopi Nako, can use these findings to develop more effective marketing strategies.